A planar multibody lumbar spine model for dynamic analysis - Morais, S. T. (2012)
The main objective is to build up a general two-dimensional multibody methodology able to model, analyze and simulate the dynamic behavior of the human lumbar spine system – in terms of vertebrae, ligaments and the IVD itself – as a basis for future applications in the study of pathological and non pathological situations, as well as in the evaluation of load and displacement performance under work of the IVD, suitable for the analysis and design of substitution implants.